Essays on John Milton : a tercentenary tribute - Milton, John, 1608-1674; Ansari, Asloob Ahmad, 1925- (Dept. of English, Aligarh Muslim University, 1976)
On the works of John Milton, 1608-1674, English poet; papers presented at a seminar organized by the Dept. of English, Aligarh Muslim University, 1974.